Characterizations of 2-Primal Ternary Semiring using Special Subsets of Ternary Semiring - Tuhfatul Janan; Irawati (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2023)
This research aims to determine the characterizations of 2-primal ternary semiring using special subsets of ternary semiring. We use literature review method to achieve these aims. We define O^' (P) and O_P^', the special subsets of ternary semiring then we determine some properties of them. We also determine the condition for O(P) and O_P in order to the special subsets are ideals of S. The last, the special subsets of ternary semiring will be used to determine the characterizations of 2-primal ternary semiring. As the results, some the characterizations were S must be a commutative super nilpotent ternary semiring and O(P)=(O(P) ) or each prime ideal P of S. Besides that, O(P)=O_P=N(P) and O_P^' must has the IFP for each prime ideal P of S.